ADAKAH HUBUNGAN ANTARA KEJADIAN NYERI SENDI LUTUT DENGAN TINGKAT KEMANDIRIAN LANSIA DI PANTI JOMPO? - Erdanela Setiawati; Budi Yulhasfi Febrianto; Amelia Fitri (Yayasan Nusantara Hasana Berdikari, 2026)
The aging process causes degenerative changes that impact the decline in physical function of the elderly, one of which is knee joint pain. Knee joint pain can inhibit the physical activity of the elderly and potentially reduce the level of independence in carrying out daily activities. This study aims to determine the relationship between the incidence of knee joint pain and the level of independence in the elderly at the Kasih Sayang Ibu Batusangkar nursing home (PSTW). The method used is an observational analytical study with a cross-sectional design. The study population was all elderly living at the Kasih Sayang Ibu Batusangkar PSTW with a sample of 52 respondents. Measurement of knee joint pain was carried out using the Numeric Rating Scale (NRS), while the level of independence was assessed using the Modified Barthel Index. Univariate data analysis is presented in the form of a frequency distribution and bivariate analysis using the Fisher's Exact test. The results of this study are the majority of respondents experienced knee joint pain (82.7%) and most had a level of independence in the non-independent category (53.8%). The results of the bivariate analysis showed a significant relationship between the incidence of knee joint pain and the level of independence in the elderly at the Kasih Sayang Ibu Batusangkar Nursing Home (PSTW) with a p value of 0.008 (p < 0.05). The conclusion of this study is that there is a relationship between the incidence of knee joint pain and the level of independence in the elderly at the Kasih Sayang Ibu Batusangkar Nursing Home (PSTW).